STRUCTURAL DEVELOPMENT POLICIES AND STRUCTURAL CHANGE IN RURAL/URBAN AREAS IN GREECE: AN INTERREGIONAL SAM ANALYSIS - Psaltopoulos, Demetrios; Balamou, Eudokia (Economics of Agriculture, 2011)
A three-area, interregional Social Accounting Matrix (SAM) model is used to assess the effects of structural policies implemented in the rural town of Archanes (Crete, Southern Greece) during the 1990s, in terms of changes in the structure of the local economy, the extent of economic impacts and their diffusion patterns to adjacent rural and urban localities. Structural changes within a time span of 10 years are estimated using a causative matrix approach, while structural decomposition analysis provides an indication of the attribution of local output growth to changes in the economic structure or final demand. Results reveal that final demand effects on gross production were more important than changes in technical coefficients. Structural policy injections was responsible for around 20.3% of gross production change in Archanes during this period. Also, structural policy specific impacts seem to be quite different, as CAP support measures are associated with comparatively high output and household income benefits for Heraklion and high output and employment benefits for N. Kazantzakis. In contrast, development measures are more successful in generating firm and household incomes in Heraklion and firm income and employment in N. Kazantzakis.